Mortality Predictors using Chest Computed Tomography Findings in COVID-19 Patients - Ali Yavuz Uzun; Yılmaz Üçüncü; Nur Hürsoy; Fatma Beyazal Çeliker; Zihni Yazıcı (Gazi Medical Journal)
Objective: The coronavirus disease (COVID) pandemic is still ongoing. Computed tomography (CT) is widely used in coronavirus disease-2019 (COVID-19) patients for lung damage determination. The aim of this study was to investigate the relationship between mortality rates and measurements of intrathoracic anatomical structures using CT images. Methods: This retrospective study was conducted in a single center and included a total of 322 cases, namely, 147 deceased and 175 surviving patients. All patients were diagnosed with COVID-19 on the basis of a positive polymerase chain reaction test. Total lung volumes, diameters of major vascular structures, comorbidity status, and laboratory blood tests were measured or determined. Total lung volumes were calculated using the range of -1024 to -300 Hounsfield Unit in the Slicer application. Results: A decrease in total lung volume was associated with a higher mortality rate (p<0.001). Increases in right and left pulmonary artery diameters were associated with high mortality rate (p=0.002 and 0.001, respectively). Increase in cardiothoracic ratio and decrease in thorax diameter were associated with high mortality rate in female patients (p=0.013 and p<0.001, respectively). It was found that patients with cardiovascular disease (p=0.043), chronic lung disease (p=0.005) and renal failure (p<0.001) had a significant mortal course. Elevated values of white blood cell count (p=0.018), aspartate aminotransferase (p<0.001), lactate dehydrogenase (p<0.001) and C-reactive protein (p<0.001) were found to be associated with high mortality rates. Conclusion: Total lung volume and intrathoracic main vascular sizes can be obtained from CT images using computer applications, and these measurements can provide an idea of the mortality rate in COVID-19 patients. In addition, comorbidity status and laboratory blood parameters can be used as prognostic markers.